Characterization of Extracellular Dextranase from a Novel Halophilic Bacillus subtilis NRC-B233b a Mutagenic Honey Isolate under Solid State Fermentation - Mona A. Esawy; Sara H. Mansour; Eman F. Ahmed; Naziha M. Hassanein; Hesham A. El Enshasy (E-Journal of Chemistry)
Bacillus subtilis NRC-B233b was isolated from Libyan honey sample proved to be a potent dextranase producer by applying solid state fermentation and utilizing corn flour as the sole carbon source. The optimized culture conditions for dextranase productions were 37°C, pH 10, 32 h, and 20% (v/w) moisture content. A unique character of this isolate is its ability to produce steady dextranase irrespective to the presence of NaCl in the medium. The addition of 0.175 Mm CrCl3 increased the enzyme production by about 4.5 fold. Further improvement in enzyme production was achieved by simple UV mutation which increased the enzyme production up to about 2842 U/g. The crude extract has been partially purified about 112-fold from crude extract by only two purification steps involving ultra-filtration. The partially purified dextranase showed its maximum activity at pH 9.2 and 70°C. It retained full activity (100%) at 75°C for one hour. Dextranase activity increased about 4 fold in the presence of 10% NaCl. This enzyme showed variable degradation effect on different types of dextran and its derivatives. The treatment of viscous sugar cane juice with the enzyme preparation resulted in clear visual dextran hydrolysis. These results suggest that the dextranase produced by Bacillus subtilis NRC-B233b is industrially applicable.